Electrode impedance changes after implantation of a dexamethasone-eluting intracochlear array. (3rd March 2020) - Needham, Karina; Stathopoulos, Dimitra; Newbold, Carrie; Leavens, Jason; Risi, Frank; Manouchehri, Shahram; Durmo, Irfan; Cowan, Robert
Abstract : Postoperative inflammation and the formation of fibrotic tissue around the intracochlear electrode array are often held responsible for negative outcomes in cochlear implant recipients. Here we test the effectiveness of intracochlear delivery of dexamethasone via a drug-eluting electrode array in reducing fibrotic tissue formation, assessed via measurement of both monopolar and four-point electrode impedance. Adult guinea pigs were bilaterally implanted with a dexamethasone-eluting array (left ear) and a standard non-eluting array (right ear). Arrays were electrically stimulated daily for 4 weeks, commencing 1 week after implantation, and impedance measured both before and after stimulation. Histological assessment of the tissue was made at the end of the 5-week period. The dexamethasone-eluting array did not reduce monopolar (MP1 + 2) electrode impedance over the course of 5 weeks, and no significant difference was observed in fibrotic tissue, new bone growth, or spiral ganglion neuron density between array types. However, four-point impedance, which provides an indication of the local environment at the neural-tissue interface, was significantly lower in the presence of dexamethasone. A strong relationship was seen between four-point and monopolar impedance for individual electrode arrays, with the exception of the standard array after daily electrical stimulation. This group instead showed a significant correlation between the final four-point impedance measure and percentage of fibrous tissue and new bone growth. In conclusion, this study demonstrated that dexamethasone influences four-point electrode impedance as well as the relationship between fibrotic tissue and impedance, and that both outcomes are shaped by daily electrical stimulation. These results suggest a change occurs at the local tissue-electrode interface in the presence of sustained, intracochlear release of dexamethasone.